(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In kazakh literature definition and the view of notions «Kylyzaman (different times)», «Zarzaman (hard times)», «Tar zaman (tight times)», «Ker zaman», «Akyrzaman (end of the world)» are determined in the article named «The image of concepts «Period (Zaman)» and «Time (Uikit)» in traditional kazakh culture and literature». The author explains and analyzes the concepts «Period» and «Time» on the basis of poet’s and storyteller’s poetry. In this article the concept «zaman» is widely explained in the writings of «Zarzaman» stream’s representatives.